Determination of residual volatile organic compounds migrated from polystyrene food packaging into food simulant by headspace solid phase microextraction-gas chromatography - Sanagi, Mohd. Marsin; Ling, Susie Lu; Nasir, Zalilah; Wan Ibrahim, Wan Aini; Abu Naim, Ahmedy (Malaysian Society of Analytical Sciences, 2008)
The residual styrene and other volatile organic compounds (VOCs) present in the polystyrene food packaging are of concern as these compounds have the potential to migrate into the food in contact. This work describes a method for quantitative determination of VOCs, namely styrene, toluene, ethylbenzene, iso-propylbenzene and n-propylbenzene that have migrated from polystyrene food packaging into food simulant by gas chromatography-flame ionization detection (GC-FID). Headspace solid phase microextraction (HS-SPME) technique was applied for migration test using water as food simulant. The effects of extraction variables including sample volume, elutropic strength, extraction temperature, extraction time, desorption time, sample agitation, and salt addition on the amounts of the extracted analytes were studied to obtain the optimal HS-SPME conditions. The optimized method was applied to test the VOCs migrated from polystyrene bowls and cups at storage temperatures ranging from 24°C to 80°C for 30 min. Styrene and ethylbenzene were found to migrate from the samples into the food simulant. The migration of analyte was found to be strongly dependent upon the storage temperature. The HS-SPME is useful as an alternative method to determine the migration of VOCs from food packaging material into food simulant.